La comodidad para el paciente crónico desde el sentir y el hacer - Yadira Cardozo-Garcia; Angela Maria Salazar-Maya; Carmen Liliana Escobar-Ciro (Universidad Francisco de Paula Santander, 2021)
Objective: TDescribe the meaning of comfort for patients with a chronic disease who are hos-pitalized in a third-level hospital in the city of Medellin. Materials and methods: Qualitative study of ethnographic approach. Fifteen interviews and forty hours of participant observation were made. The participants were patients with a chronic disease, hospitalized in internal medicine services of an institution in Medellin (Colombia). A double-check of the reports were made for the analysis of the data; through their codification the concepts were identified in order to categorize them, associating the categories with their respective subcategories. Results: The meaning of comfort built by the patient with a chronic disease is an extensive concept, which considers physical, social, emotional, sociocultural, and environmental as-pects. These must be considered during the health care provided to achieve welfare for the patient and the caregiver during the hospitalization time. Conclusions: cComfort is a care component that the nurse must provide. Thereon, it is important to understand the means and ways to provide comfort to hospitalized patients, in order to achieve greater welfare of the patients during their stay at the hospital. Likewise, the healthcare institutions should listen to the patients to be able to make adequate adjustments for a pleasant and less traumatic hospi-talization experience for patients with chronic diseases